2017
DOI: 10.1186/s11671-017-2335-y
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enhanced H2 Sensing Performance of Few-Layer MoS2/SiO2/Si Heterojunctions by Surface Decoration of Pd Nanoparticles

Abstract: A novel few-layer MoS2/SiO2/Si heterojunction is fabricated via DC magnetron sputtering technique, and Pd nanoparticles are further synthesized on the device surface. The results demonstrate that the fabricated sensor exhibits highly enhanced responses to H2 at room temperature due to the decoration of Pd nanoparticles. For example, the Pd-decorated MoS2/SiO2/Si heterojunction shows an excellent response of 9.2 × 103% to H2, which is much higher than the values for the Pd/SiO2/Si and MoS2/SiO2/Si heterojunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…In addition, the Pd NP/MoS 2 composites showed a high H 2 selectivity against NH 3 , acetone (CH 3 COCH 3 ), and ethanol (C 2 H 5 OH) (Figure 24e), although the concentration of NH 3 (50 ppm) was different to other gas molecules (5%). This study demonstrated the feasibility of Pd/MoS 2 composites for H 2 sensors and stimulated the development of various Pd/TMD composites for H 2 sensors, such as Pd/MoS 2 , 249,255 Pd/ WS 2 256 , and Pd/SnO 2 /MoS 2 257 . These Pd/TMD composites showed interesting and efficient H 2 sensing properties.…”
Section: Other Materialsmentioning
confidence: 76%
See 1 more Smart Citation
“…In addition, the Pd NP/MoS 2 composites showed a high H 2 selectivity against NH 3 , acetone (CH 3 COCH 3 ), and ethanol (C 2 H 5 OH) (Figure 24e), although the concentration of NH 3 (50 ppm) was different to other gas molecules (5%). This study demonstrated the feasibility of Pd/MoS 2 composites for H 2 sensors and stimulated the development of various Pd/TMD composites for H 2 sensors, such as Pd/MoS 2 , 249,255 Pd/ WS 2 256 , and Pd/SnO 2 /MoS 2 257 . These Pd/TMD composites showed interesting and efficient H 2 sensing properties.…”
Section: Other Materialsmentioning
confidence: 76%
“…Table summarizes the sensing performances of TMD-based H 2 sensors operated at RT in air. ,, , Their sensing properties are inferior to other sensing materials, such as Pd and metal oxides. However, since TMDs have various fascinating features as chemical sensors, such as high surface area, 2D structure, tunable electrical properties, and operation at RT, , we expect that the TMD-based H 2 sensors can grow rapidly in the future.…”
Section: Other Materialsmentioning
confidence: 99%
“…Many different sensing technologies have been developed for H 2 sensing [ 7 , 8 , 9 ] and semiconductor-based H 2 sensors mainly present high sensitivity, quick response, and good stability based on their physical and electrochemical characteristics [ 10 , 11 , 12 , 13 , 14 ]. Commonly, the exceptional physical, optical, and electrical properties of 2D semiconductors, such as high surface to volume ratios and numerous active sites, lead to promising gas sensing performance (i.e., gas selectivity, excellent response, durability, and quick response and recovery) because of a change in charge density concentration near or on the sensing layer [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductor-based gas sensors have the benefits of low cost, small size, and low power consumption. Various semiconductor materials have been utilized to implement hydrogen sensors [4][5][6][7][8][9][10], among which GaN is an attractive material for a hydrogen sensor operating at high temperatures because of its wide energy bandgap with low intrinsic carrier density [11][12][13]. The low intrinsic carrier density allows GaN to maintain its semiconductor properties in high-temperature environments.…”
Section: Introductionmentioning
confidence: 99%